Uniform Convergence Analysis of a Higher Order Hybrid Stress Quadrilateral Finite Element Method for Linear Elasticity Problems (Advances in Applied Mathematics and Mechanics, 2018)
This paper derives a higher order hybrid stress finite element method onquadrilateral meshes for linear plane elasticity problems. The method employs continuouspiecewise bi-quadratic functions in local coordinates to approximate the displacementvector and a piecewise-independent 15-parameter mode to approximate thestress tensor. Error estimation shows that the method is free from Poisson-locking andhas second-order accuracy in the energy norm. Numerical experiments confirm thetheoretical results.